Effects of microclimate on soil bacterial communities across two contrasting timberline ecotones in southeast Tibet. (8th September 2015) - Yuan, Y. L.; Si, G. C.; Wang, J.; Han, C. H.; Zhang, G. X.
Summary: The Sergyemla Mountains have unique timberline patterns. Abies georgei var. smithii (Viguie & Gaussen) and Juniperus saltuaria (Rehder & E. H. Wilson) dominate the north‐facing and south‐facing slopes of a U‐shaped valley, respectively. Although these two timberlines represent the world's highest natural tree lines, little is known about the structure of their soil bacterial communities and the factors that control them. To characterize and compare the soil bacterial communities of two timberline ecotones with different spatial orientations, we investigated their structures by terminal restriction fragment length polymorphism analysis and sequencing methods. We found that the structures of the soil bacterial communities differed significantly between the two opposite slopes, and the difference between the bacterial communities correlated primarily with soil carbon:nitrogen ratios. This probably relates to differences in the microclimate (mean soil temperature) between the two aspects in the world's highest timberline ecotones. In addition, the structures of soil bacterial communities also differed significantly with soil depth, and total nitrogen content had the greatest effect on the bacterial communities. In this region, soil temperature rather than mean annual precipitation has a major effect on the structures of soil bacterial communities. Microclimate differences (mainly differences in soil temperature) between the two opposite slopes might indicate that an amplitude increase of 2°C in soil temperature could change the structures of soil bacterial communities by changing the status of soil carbon and nitrogen in these timberline ecotones.